Effects of Aspirin in Rats With Ouabain Intracerebral Treatment—Possible Involvement of Inflammatory Modulation? - Zhang, Lin; An, Li-Ting; Qiu, Yan; Shan, Xiao-Xiao; Zhao, Wen-Li; Zhao, Jing-Ping; Li, Le-Hua; Lang, Bing; Wu, Ren-Rong (Frontiers in Psychiatry, 2019)
Bipolar disorder (BD) is a chronic and refractory disease with high probability of morbidity and mortality. Although epidemiological studies have established a strong association between BD and immune dysfunction, the precise aetiology is still debatable and the underpinning mechanism remains poorly investigated and understood. In the present study, manic-like symptoms of BD were induced in rats after intracerebroventricular administration of ouabain. Aspirin, a commonly used anti-inflammatory agent, was used to treat the induced manic-like symptoms and inflammation. Concentrations of a spectrum of inflammatory cytokines were examined by enzyme-linked immunosorbent assay in both plasma and brain tissues and expression of Toll-like receptor 3 and 4 were determined in rat brains. Locomotor activity was monitored with open field test to assess the effects of ouabain challenge and to evaluate the treatment efficacy of aspirin. Ouabain administration recapitulated many mania-like features such as increased stereotypic counts, travelling distance in open field test, and decreased expression of brain derived neurotrophic factor, INF-γ and TLR3 which were frequently found in patients with BD. These abnormalities could be partially reversed by aspirin. Our findings suggest that aspirin could be used as a promising adjunctive therapy for bipolar disorder.